Endoscopic resection of early esophageal tumors in patients with cirrhosis or portal hypertension: a multicenter observational study - Simonnot, Mathilde; Deprez, Pierre H.; Pioche, Mathieu; Albuisson, Eliane; Wallenhorst, Timothée; Caillol, Fabrice; Koch, Stéphane; Coron, Emmanuel; Archambeaud, Isabelle; Jacques, Jérémie; Basile, Paul; Caillo, Ludovic; Degand, Thibault; Lepilliez, Vincent; Grandval, Philippe; Culetto, Adrian; Vanbiervliet, Geoffroy; Camus Duboc, Marine; Gronier, Olivier; Leal, Carina; Albouys, Jérémie; Chevaux, Jean-Baptiste; Barret, Maximilien; Schaefer, Marion (Endoscopy, 2023)
Background Liver cirrhosis and esophageal cancer share several risk factors, such as alcohol intake and excess weight. Endoscopic resection is the gold standard treatment for superficial tumors. Portal hypertension and coagulopathy may increase the bleeding risk in these patients. This study aimed to assess the safety and efficacy of endoscopic resection for early esophageal neoplasia in patients with cirrhosis or portal hypertension.Methods This retrospective multicenter international study included consecutive patients with cirrhosis or portal hypertension who underwent endoscopic resection in the esophagus from January 2005 to March 2021.Results 134 lesions in 112 patients were treated, including by endoscopic submucosal dissection in 101 cases (75 %). Most lesions (128/134, 96 %) were in patients with liver cirrhosis, with esophageal varices in 71 procedures. To prevent bleeding, 7 patients received a transjugular intrahepatic portosystemic shunt, 8 underwent endoscopic band ligation (EBL) before resection, 15 received vasoactive drugs, 8 received platelet transfusion, and 9 underwent EBL during the resection procedure. Rates of complete macroscopic resection, en bloc resection, and curative resection were 92 %, 86 %, and 63 %, respectively. Adverse events included 3 perforations, 8 delayed bleedings, 8 sepsis, 6 cirrhosis decompensations within 30 days, and 22 esophageal strictures; none required surgery. In univariate analysis, cap-assisted endoscopic mucosal resection was associated with delayed bleeding (P = 0.01).Conclusions In patients with liver cirrhosis or portal hypertension, endoscopic resection of early esophageal neoplasia appeared to be effective and should be considered in expert centers with choice of resection technique, following European Society of Gastrointestinal Endoscopy guidelines to avoid undertreatment.